Pengembangan Kapasitas Sumber Daya Manusia BUMDESA Di Kabupaten Tulungagung - Sony Hartono; Oke Wibowo; Antonius Ragil Kuncoro (SULUH: Jurnal Abdimas, 2024)
Currently, in Tulungagung, East Java, many village-owned enterprises (Bumdesa) are still facing challenges in financial administration of Bumdesa financial reports that conform to the applicable accounting standards. One of the reasons for this is the shortage of human resources who possess expertise in the field of accounting. The method employed to expedite the development of human resources capable of creating financial reports in accordance with existing accounting standards is by conducting a training of trainers program for 20 Bumdesa administrators in Tulungagung. Subsequently, these 20 trained administrators become trainers themselves to impart their acquired knowledge to all Bumdesa representatives in Tulungagung. Online mentoring continues for a duration of three months. The outcome of this series of community service activities is that Tulungagung district has significantly large pool of human resources managing Bumdesa who are capable of producing financial reports. Ultimately, with an increasing number of Bumdesa administrators who understand the proper and correct management of Bumdesa finances, it is hoped that Bumdesa in Tulungagung will grow more rapidly and robustly, and be able to contribute significantly more to the improvement of the welfare of rural communities.